The Correspondence of the Senses and its Effect on Shaping the Poetic Image. Mahdi Nusair’s Poetry is an Example - Al-Kharsh‎, Ahmad Ghaleb; Al-Kayed, Ahmed Faisal (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to reveal the phenomenon of the correspondence of the senses in the poetry of Mehdi Nusair and its impact on the formation of his poetic images. The researchers discussed one of the artistic phenomena that distinguished the poet Mehdi Nusair in his poems. Methods: The researchers followed the descriptive analytical approach to study the phenomenon of communication of the senses in the poetry of Mehdi Nusair, where they extrapolated the phenomenon of sending the senses in some poetic texts in Mehdi Nusair’s poems, which largely reflects the nature of this phenomenon and his role in shaping his poetic images. Results: The phenomenon of correspondence of the senses varied in the poetry of Mahdi Nusair, as it appeared in his poems as a prominent poetic feature with its various connotations. From an artistic standpoint, this phenomenon contributed to solidifying the artistic structure in the poet’s poems and strengthening their links to produce diverse aesthetic images, expressive poetic visions, and a special pictorial language that blended the spirit Sensation and imagination formed different types of artistic images with different semantic shifts. Conclusions: The study concluded that the Jordanian poet Mahdi Nusair was able to employ the phenomenon of correspondence of the senses in his poems to produce types of poetic images with a distinctive artistic structure, and to express through this phenomenon his psychological, intellectual, and human visions.